Synthetic efforts towards the natural products brocazine F and G - Hulangamuwa, Chathurangani Wasundara (Kansas State University, 2020)
The brocazines are a family of natural products bearing a disulfide diketopiperazine core that was isolated by Meng et al in 2014 and 2016 from an endophytic fungus derived from the marine mangrove plant Avicennia marina named Penicillium brocae MA-231. Seven different brocazines (A-G) and three different spirobrocazines were isolated, and of those brocazine F showed the strongest activity against prostate cancer cell line DU145 (IC₅₀ of 1.7 μM) and lung cancer cell line NCI-H460 (IC₅₀ of 0.89 μM). Brocazine G showed strong activity against ovarian carcinoma cell line A2780 (IC₅₀ of 0.664 μM), Ovarian endometrioid adenocarcinoma A2780 CisR cells (IC50 of 0.661 μM) as well as possessing strong and selective activity against human pathogen Staphylococcus aureus (MIC of 0.25 μg/mL). Given the potent cytotoxicity of brocazine F and G and their intriguing polycyclic core structure, our laboratory devised a total synthesis route to access this family. By focusing on these compounds, we envision the construction of a screening library yielding a new series of small molecules; which can be accessed through the intermediates of the total synthesis route employed for the construction of brocazine F and G. Each intermediate will serve as the starting material for a unique set of small molecules, structurally different from the original natural product, but potentially having unique and potent biological activity. Therefore, the goal of this dissertation is to establish a reliable and reproducible route to access the brocazine family of diketopiperazine (DKP) natural products, from which the intermediates can be amendable for chemical derivatization for complex screening library construction.
Keywords: organic chemistry; total synthesis